REAL TIME VEHICLE DETECTION AND COUNTING USING MACHINE LEARNING (International Journal of Food and Nutritional Sciences, 2022)
Vehicle detection and counting are turning out to be progressively significant in the field of Highwaymanagement. In any case, because of the various sizes of vehicles, their identification stays a test that straightforwardly influences the exactness of vehicle counts. To resolve this issue, we propose a vehicle detectionsystem and counting framework.